Satellite radar imagery for monitoring inland wetlands in boreal and sub-arctic environments. - Bartsch, Annett; Kidd, Richard A; Pathe, Carsten; Scipal, Klaus; Wagner, Wolfgang (PANGAEA, 2007)
An area in central Siberia (partial coverage of Turukhansky und Yeniseysky districts) was investigated using satellite data. It covers freshwater ecosystems of non-forested peatlands in boreal forests. The satellite data represent the growing seasons of 2003/2004. Microwave data were acquired by the Advanced Synthetic Aperture Radar (ASAR) instrument onboard ENVISAT. The multi-temporal capabilities and resolution (150mx150m in WS mode) of the ASAR wide swath mode enabled the detection of dynamic features >2ha over this vast area. Scatterometer (QuikScat) data could be employed to distinguish hydro-periods. Wetland types have been identified on the basis of seasonal changes in backscatter. Results for peatlands have been compared with Russian forest inventory data which contain information on wetland distribution.
Wetlands in central Siberia from ASAR WS 2003, link to shapefiles
Keywords: Turukhansky_and_Yeniseysky_districts